Konfrontasi Iran-Israel dalam Perspektif Realisme Klasik - Satryo Pringgo Sejati; Hakim, Ahmad Burhan (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
The escalation of the conflict between Israel and Palestine can be called Hamas from day to day. The escalation turned out to involve another country, namely Iran as one of the countries in the Middle East that has strong military defense resources. As a Muslim and threatened by Israeli actions in Palestine, there were also several defiant statements issued by the Israeli authorities that eventually made Iran directly involved in the war that occurred between Palestine and Israel. This is not only the issue of Islam as a causal factor, but Israel tends and often conducts political confrontations with Iran, so that the country is directly involved. Israel's military's notoriously strong defenses were finally rendered powerless by hundreds of rockets launched from Tehran. Tel Aviv was finally devastated by the attack. This proves that Iran's national interests are being directly disturbed by Israel, so the action of Iran is an active reaction to the problem. The national interest is one of the important elements in the approach and theory of classical realism in politics and international relations. Thus, it can be an analytical knife if the theory is used. The research method used in this article is a qualitative research method using literature studies as a way to obtain and analyze the data needed. The primary data and secondary data are prepared by the author to support the data collection in this article. The confrontation between Iran and Israel over the past year, namely in 2025, has increased, they launched rockets and missiles at each other to attack their respective capitals, namely Tehran (Iran) and Tel Aviv (Israel). So the occurrence of the confrontation has indeed become a natural thing. When Iran as an independent country was disturbed by Israel, which has often waged wars against Palestine. Iran also wants to prove to the world that the country has a strong military defense system.